Lower spinal levels and male sex are associated with greater epidural blood patch volume in spontaneous intracranial hypotension - Woo-Seok Ha; JaeWook Jeong; Seungwon Song; Jungyon Yum; Soomi Cho; Hee Jung Kim; Min Kyung Chu (The Journal of Headache and Pain)
Abstract Background The epidural blood patch (EBP) is the treatment of choice for spontaneous intracranial hypotension (SIH). Studies have shown that targeted EBP is more effective than blind EBP. Additionally, a greater volume of injected blood during EBP has been associated with better therapeutic outcomes. However, symptoms such as back pain often prevent achieving the desired blood volume. This study aimed to analyse factors influencing the tolerable EBP volume, including structural, clinical, and psychological factors. Methods This retrospective study included patients diagnosed with SIH who underwent single-level EBP at a tertiary care centre from 2019 to 2024. Data collected encompassed target levels, cross-sectional area, types of EBP, demographics, imaging findings, maximum intensity of orthostatic headache, Headache Impact Test-6, psychological state (Generalized Anxiety Disorder-7 and Patient Health Questionnaire-9), and somatic symptom burden (Widespread Pain Index and Symptom Severity Scale). A linear mixed model (LMM) was used to investigate factors influencing the total injected blood volume, accounting for repeated EBP procedures per patient. Sensitivity analysis was performed to assess model robustness. Results A total of 103 EBP procedures from 53 patients (62% female; mean age, 39.9 ± 11.1 years) were analysed. The results of the LMM revealed that lower spinal levels (beta = 0.306, P = 0.029) and male sex (beta = 4.347, P = 0.024) were significantly associated with higher tolerable EBP volumes. Psychological factors or somatic symptom burden did not have a significant impact on the injected blood volume. In the sensitivity analysis, the number of EBP procedures (beta = -0.804, P = 0.001) was also significantly associated with lower tolerable EBP volume. Conclusions Lower spinal levels and male sex were associated with higher tolerable EBP volumes in patients with SIH. The trade-off between spinal level and tolerable EBP volume should be considered when developing targeted blood patch strategies and evaluating their efficacy. Graphical Abstract